Activation mechanism of lead ion in the flotation of stibnite. (April 2018) - Cao, Qinbo; Chen, Xiumin; Feng, Qicheng; Wen, Shuming
Graphical abstract: Highlights: The floatability of stibnite was improved by treatment with the Pb 2+ ion. Pb 2+ could adsorb at five different sites on the stibnite surface. Xanthate further interacted with the Pb atom at the Pb-activated surface. Xanthate preferred to adsorb onto the Pb-activated surface. Abstract: The flotation of stibnite with Pb 2+ as an activator was examined with micro-flotation tests, inductively coupled plasma mass spectrometry (ICP-MS) experiments and density functional theory (DFT) calculations. It was found that at a pH of 6.5, the addition of Pb(NO3 )2 notably improved the flotation efficiency of stibnite with butyl xanthate (BX). At a pH of 6.5, Pb 2+ was the dominant species adsorbing at the stibnite surface. DFT calculations implied that Pb 2+ could adsorb at five different sites on the stibnite surface. Furthermore, BX could adsorb onto the Pb sites at the Pb-activated surface and the Sb sites of the un-activated surface, while the adsorption of BX on the Pb-activated surface is more stable. Partial density of states (PDOS) analysis revealed that the poor overlapping between the S 3p orbital of BX and the Sb 5s orbital accounts for the weak interaction between BX and the un-activated surface. For the Pb-activated surface, the Pb 6p orbital and the S 3p orbital of BX were efficiently overlapped with each other, resulting in a relatively stronger interaction between BX and the activated surface. The DFT simulation provides a deep insight into the role of Pb 2+ during the activation flotation of stibnite.